Assessing outcomes of enhanced chronic disease care through patient education and a value-based formulary study (ACCESS)—study protocol for a 2×2 factorial randomized trial. (December 2015) - Campbell, David; Tonelli, Marcello; Hemmelgarn, Brenda; Mitchell, Chad; Tsuyuki, Ross; Ivers, Noah; Campbell, Tavis; Pannu, Raj; Verkerke, Eric; Klarenbach, Scott; King-Shier, Kathryn; Faris, Peter; et al.
Abstract Background Chronic diseases result in significant morbidity and costs. Although medications and lifestyle changes are effective for improving outcomes in chronic diseases, many patients do not receive these treatments, in part because of financial barriers, patient and provider-level knowledge gaps, and low patient motivation. TheAssessing outcomes of enhanced chronic disease care through patient education and a value-based formulary study (ACCESS) will determine the impact of two interventions: (1) a value-based formulary which eliminates copayment for high-value preventive medications; and (2) a comprehensive self-management support program aimed at promoting health behavior change and medication adherence, combined with relay of information on medication use to healthcare providers, on cardiovascular events and/or mortality in low-income seniors with elevated cardiovascular risk. Methods The ACCESS study will use a parallel, open label, factorial randomized trial design, with blinded endpoint evaluation in 4714 participants who are over age >65 (and therefore have drug insurance provided by Alberta Blue Cross with 30 % co-payment); are at a high risk for cardiovascular events based on a history of any one of the following: coronary heart disease, prior stroke, chronic kidney disease, heart failure, or any two of the following: current cigarette smoking, diabetes mellitus, hypertension, or hypercholesterolemia; and have a household income <Can$50, 000. This 3-year study is powered to detect a minimal clinically important relative risk reduction of 12 % in the composite clinical outcome of all-cause mortality, nonfatal myocardial infarction, nonfatal stroke, need for coronary revascularization, and hospitalizations for chronic disease-related ambulatory care sensitive conditions, each of which will be assessed using healthcare administrative data. Secondary outcomes will include quality of life and healthcare costs. Discussion Given identified gaps in care in chronic disease, and the frequency of financial and knowledge-related barriers in low-income Albertans, this study will test the impact of providing free high-value preventive medications (i.e., value-based insurance) and a tailored self-management education and facilitated relay strategy on outcomes and costs. By measuring the impact on both health outcomes and costs, as well as the impact on reducing health inequities in this vulnerable population, our study will facilitate informed policy decisions. Trial registration Clinicaltrials.gov:NCT02579655 . Registered Oct 15, 2015.